Models of Care for Inflammatory Bowel Disease: A National Cross-sectional Survey to Characterize the Landscape of Inflammatory Bowel Disease Care in Canada. Issue 4 (30th November 2022) - Miles, Matthew; Peña-Sánchez, Juan Nicolás; Heisler, Courtney; Cui, Yunsong; Mathias, Holly; Stewart, Michael; Jones, Jennifer L
Abstract: Background: Collaborative care models improve inflammatory bowel disease (IBD) patient outcomes, yet little is known about the capacity or available resources to deliver such model of care in Canada. We aimed to describe the structure and process characteristics of clinical care delivery models for IBD across Canada, including the number of collaborative care centers. Methods: A cross-sectional study was conducted between November 2017 and October 2018 through an online survey. This survey was distributed to gastroenterologists at community and academic centers across Canada who provide care for IBD patients. Comparisons between collaborative and non-collaborative centers were analyzed using chi-squares or t -tests. Descriptive statistics of respondent demographics were also generated. Results: Seventy-two gastroenterologists from 62 unique IBD centers completed the survey. A total of 7 unique collaborative centers and 55 unique non-collaborative centers were identified. There were significant differences between collaborative and non-collaborative centers in some aspects of access to IBD care, patient assessment and referral process, and patent education and empowerment. Notably, very few centers had processes for implementing and evaluating evidence-based clinical pathways, and auditing quality indicators. Conclusions: Our findings identify areas for improving the quality of IBD care in Canada. Expanding the number of and access to collaborative care centers in Canada is needed, in addition to increased focus on patient education, communication, and implementation of evidence-based care pathways. Lay Summary: Collaborative care is an important innovation in providing quality inflammatory bowel disease (IBD) care, yet few collaborative care centers exist in Canada. More collaborative care centers focusing on patient education, communication, and implementing evidence-based care are needed to improve IBD patient care.